2015
DOI: 10.1158/2159-8290.cd-14-0697
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Residual Estrogen Receptor Availability during Fulvestrant Therapy in Patients with Metastatic Breast Cancer

Abstract: It is unknown whether the current dose of fulvestrant, an estrogen receptor (ER) antagonist, is suffi cient for maximal ER downregulation in patients with metastatic breast cancer. We performed a feasibility study to assess ER availability before and during fulvestrant. Sixteen patients with ER-positive metastatic breast cancer underwent positron emission tomography/ computed tomography (PET/CT) at baseline (scan 1), day 28 (scan 2), and day 84 (scan 3) to monitor tumor [ 18 F]fl uoroestradiol (FES) uptake. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(146 citation statements)
references
References 30 publications
4
141
1
Order By: Relevance
“…In the metastatic setting, fulvestrant has been shown to be effective as a single agent and a recent study demonstrated that the increased dose of 500 mg fulvestrant is superior to the historical 250 mg dose in terms of overall survival (8,12,13). However, there is evidence to suggest that even at the 500 mg dose, suboptimal occupancy of the estrogen receptor can occur in some patients, which may correlate with an earlier progression of disease (14). These data, combined with fulvestrant's intramuscular route of administration underscore the need for a novel orally bioavailable SERD for the treatment of ER þ breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the metastatic setting, fulvestrant has been shown to be effective as a single agent and a recent study demonstrated that the increased dose of 500 mg fulvestrant is superior to the historical 250 mg dose in terms of overall survival (8,12,13). However, there is evidence to suggest that even at the 500 mg dose, suboptimal occupancy of the estrogen receptor can occur in some patients, which may correlate with an earlier progression of disease (14). These data, combined with fulvestrant's intramuscular route of administration underscore the need for a novel orally bioavailable SERD for the treatment of ER þ breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the degree of ER degradation achieved with fulvestrant appears suboptimal: paired biopsy data indicate that therapy at the initially approved 250 mg dose results in reduction of ERα levels to 50% of baseline, rather than to undetectable levels (Robertson et al 2001). Even at the higher dose of 500 mg, serial [(18)F] fluoroestradiol PET scans reveal incomplete suppression of estrogen uptake in 38% of patients (van Kruchten et al 2015). Taken together, these factors indicate a need to develop next-generation SERDs that would not only be orally bioavailable for patient convenience but also exhibit more efficient receptor degradation.…”
Section: Fulvestrant Clinical Studiesmentioning
confidence: 99%
“…There may be advantages to more limited isoform selectivity in some tumors, as this may facilitate an increase in the therapeutic drug exposure without increasing off-target side effects. Tumors with activating mutations in the PIK3CA gene would be expected to be sensitive to a drug selectively inhibiting the p110α isoform, whereas PI3K signaling in PTEN-deficient tumors appears more dependent on the p110β isoform and may benefit from pan-class 1 inhibition (Wee et al 2008, Jiang et al 2010, Vanhaesebroeck et al 2010, Schwartz et al 2015. More selective compounds are entering clinical trials.…”
Section: Selective Pi3k Inhibitorsmentioning
confidence: 99%
“…62 This tracer has been reported as useful for imaging estrogen-dependent endometrial cancer and breast cancer. 63 F-FES ratio may offer an accurate index for differentiating endometrial diseases, based on the fact that endometrial carcinoma has reduced estrogen dependency and accelerated glucose metabolism following progression to higher stages or grades. This ratio offers great accuracy in predicting high-and low-risk carcinoma or diagnosing endometrial carcinoma and hyperplasia.…”
Section: Uterine Endometrial Cancermentioning
confidence: 99%